Answer:
2
Explanation:
So we are going to do
(sum of parts of the secant)(part on outside)=(sum of parts of the secant)(part on outside) .
This is what you get from doing that:
(1+x+4)(x+4)=(11+x+1)(x+1)
Simplifying:
(x+5)(x+4)=(x+12)(x+1)
We could see which value of x makes both side the same.
Choice 1: Plug in 2 for x:
(2+5)(2+4)=(2+12)(2+1)
(7 )(6 )=( 14 )(3)
42 = 42
This equation is true.
Choice 2: Plug in 3 for x:
(3+5)(3+4)=(3+12)(3+1)
( 8)( 7)=( 15)( 4)
56 = 60
This equation is not true.
Choice 3: Plug in 6 for x:
(6+5)(6+4)=(6+12)(6+1)
( 11 )( 10 )=( 18 )(7 )
110 = 126
This equation is not true.
Choice 4: Plug in 7 for x:
(7+5)(7+4)=(7+12)(7+1)
(12 )( 11 )=( 19 )(8)
132 =152
This equation is not true.